Thermal induced NDC of electron swarms in N2 and N2-like gases: the role of temperature and collision operator approximations. (7th November 2019) - Casey, M J E; Cocks, D G; Boyle, G J; Brunger, M J; Dujko, S; Urquijo, J de; White, R D
Abstract: The role of temperature on the existence of negative differential conductivity (NDC) is investigated using Boltzmann equation calculations of electron swarms in gaseous nitrogen. This effect has been observed previously in both experimental results and calculations, with the important role of superelastic rotational collisional processes in this phenomenon being examined in this work. A simple analytic model cross-section set is employed to elucidate the role of de-excitation processes in NDC, with complementary physics identified in N2 . The criterion of Robson (1984 Aust. J. Phys. 37 35) for predicting the occurrence of NDC using only knowledge of the collisional cross-sections is utilised for both the model system and N2, and found to be in excellent agreement with our simulated appearance of NDC. Finally, we also report on the impact of anisotropy in the very low threshold scattering channels on the transport coefficients, examine the finite difference collision operator of Frost and Phelps (1962 Phys. Rev. 127 1621) for the inelastic channel, in particular its neglect of recoil, and assess other assumptions utilised in existing Boltzmann equation solvers.